Expression of Markers of Semen Quality and Fertility in Stallions of the Crioulo Breed - Trevisan Roese, Isabela; La Cruz Bueno, Verônica; Boll de Araujo Bastos, Henrique; Costa Mattos, Rodrigo; Fiala Rechsteiner, Sandra (Acta Scientiae Veterinariae, 2023)
Background: Mammalian spermatozoa contain a complex RNA population able to regulate spermatogenesis and play a role in the fertilization process. However, little is known about genetic factors and their role in fertility. Discovering novel molecular markers is necessary because semen quality parameters and routine exams still fail at detecting cases of subfertility. The objective of this study was to assess the relationship between the expression of the genes SPA17, TNF and TIMP2 by spermatozoa and semen quality, fertility, and motility parameters of sperm cells after thawing in stallions of the Crioulo breed. Materials, Methods & Results: Analysis were performed on ejaculates from 40 stallions whose fertility was evaluated by checking their reproductive history, considering 30 inseminations for each animal. One mL of each ejaculate was reserved for fresh semen analysis, and the remaining volume was split into 2 samples; 1 of these samples was stored for gene expression analysis, and the other was cryopreserved. Sperm cell motility was analyzed using the computer-assisted semen analysis system. Sperm pathology analyses, hypoosmotic tests, and fluorescence tests were also performed. For gene expression analysis, mRNA was extracted for quantitation of expression of genes of interest by quantitative real-time polymerase chain reaction (qPCR). The results from qPCR assays were determined using an absolute standard curve [formula=10^(target ct - standard CT)/slope]. Statistical analysis was performed using Pearson correlation. Expression of SPA17 was positively correlated with functional integrity of the plasma membrane (r = 0.602; P = 0.004), structural integrity of the plasma membrane (r = 0.590; P = 0.004), conception rate (r = 0.454; P = 0,007), and total motility (r = 0.522; P = 0.001); it was negatively correlated with immobile sperm cells (r = -0.558; P = 0.006), and sperm cells with major defects (r = 0.4907; P = 0.012). Expression of TNF in sperm cells thawed after cryopreservation was positively correlated with curvilinear velocity (VCL) [r = 0.5147; P = 0.02], straight-line velocity (VSL) [r = 0.4714; P = 0.03], and average path velocity (VAP) [r = 0.4907; P = 0.02]. A positive correlation between TIMP2 expression and beat-cross frequency (BCF) was found [r = 0.408; P = 0.02]. Discussion: The positive correlations between SPA17 expression and the parameters total motility and conception rate may be related to the previously reported interaction of SPA17 with the zona pellucida, which facilitates penetration of the sperm cell into the oocyte. The positive correlations between expression of SPA17 and the parameters structural integrity of the plasma membrane and functionality of the plasma membrane are connected to characteristics important for viability of the sperm cell at the moment of conception, such as avoiding thermal shock and maintaining fluidity of the plasma membrane. Expression of TNF was positively correlated with sperm cell velocities after cryopreservation. TNF exerts a series of biological activities in different cell types. TNF regulates energy metabolism, especially in lipid homeostasis; it can be involved with plasma membrane phospholipid metabolism and reduce damage to the sperm cell during the cryopreservation process. We conclude that expression of SPA17 in equine sperm cells can be used as a biomarker for semen quality and fertility of stallions, while expression of TIMP2 can be used as a biomarker for beat-cross frequency. Expression of TNF was associated with better sperm cell survival rates after the cryopreservation process. Keywords: stallion, fertility, concept rate, seminal quality, expression gene. Título: Expressão de marcadores de qualidade seminal e fertilidade de garanhões da raça Crioula Descritores: garanhão, fertilidade, taxa de prenhez, qualidade seminal, expressão gênica.